Developing Game-based Learning on Unity in Diversity using GameMaker Studio - Siregar, Hisar; Siregar, Nurliani (International Journal of Educational Technology and Artificial Intelligence, 2024)
Learning “Unity in Diversity” is hard to implement. Students are bored with what the teacher says. Learning is not enjoyable, especially for the young generation. In an increasingly diverse world, fostering an understanding and appreciation of different cultures, perspectives, and backgrounds is paramount. This article introduces the development of a game-based learning approach to promote diversity education, using GameMaker Studio as the primary development tool. With the potential to reach and engage a broad audience, game-based learning offers a unique platform to explore and celebrate diversity. This article outlines the critical components of the development process, from conceptualization to implementation, highlighting the advantages of using GameMaker Studio. The article discusses the significance of incorporating technology and gamification into diversity education and offers insights into the practical implementation of such educational games. Developing the application, the researcher conducts qualitative approaches to the Game Development Life Cycle (GDLC), which contains six stages: initiation, pre-production, production, testing, beta, and release. It is the utmost hope that the new game-based earning model could facilitate more accessible, more fun, and exciting things, especially for youth. Research findings show that mobile-based learning, including games, are the most feasible model to be implemented.